Persuasive Language Used on Advertisements of Instagram Posts - Rizky Vita Losi; Sisi Rosida (Titian: Jurnal Ilmu Humaniora, 2022)
This study aimed to find out the persuasive language on Starbucks advertisements on Instagram posts. The category of persuasive language was referred to Lamb's theory (2014). By using descriptive qualitative method, the researcher collected seventy data of Starbucks advertisements on Instagram posts. Then, the data were analyzed by categorizing and interpreting them into the correct categories. The research result and discussion showed that from 70 data which were taken from Starbucks advertisements on Instagram posts, there were 60 data found by the distribution as follow: 5 data of Alliteration, 6 data of Colloquial Language, 7 data of Connotation, 6 data of Evidence, 6 data of Hyperbole, 8 data of Inclusive Language, 5 data of Imagery, 7 data of Pun, 4 data of Repetition, and 6 data of Simile. The most used of persuasive language on Starbucks advertisements on Instagram posts was Inclusive Language because the company often use everyday or informal language to connect closer with the customers.